Genetic variability among 18 cultivars of cooking bananas and plantains by RAPD and ISSR markers - YUYU SURYASARI POERBA; FAJARUDIN AHMAD (Society for Indonesian Biodiversity, 2010)
Poerba YS, Ahmad F (2010) Genetic variability among 18 cultivars of cooking bananas and plantains by RAPD and ISSR markers. Biodiversitas 11: 118-123. This study was done to assess the molecular diversity of 36 accessions (18 cultivars) of the plantain and cooking bananas (Musa acuminata x M. balbisiana, AAB, ABB subgroups) based on Random amplified polymorphic DNA (RAPD) and and Inter Simple Sequence Repeats (ISSR) markers and to determine genetic relationships in the bananas. RAPD and ISSR fingerprinting of these banana varieties was carried out by five primers of RAPDs and two primers of ISSRs. RAPD primers produced 63 amplified fragments varying from 250 to 2500 bp in size. 96.82% of the amplification bands were polymorphic. ISSR primers produced 26 amplified fragments varying from 350 bp to 2000 bp in size. The results showed that 92.86% of the amplification bandswere polymorphic. The range of genetic distance of 18 cultivars was from 0.06-0.67.Key words: RAPD analysis, Musa acuminata, Musa balbisiana, plantain, cooking bananas.